Responses to the COVID-19 pandemic: Impacts on higher education in East Asia - Park, Yuhyun; Baldry, T. Adam; Amarilla, Jessica (Journal of International Students, 2025)
The COVID-19 pandemic disrupted higher education in East Asia, prompting institutions in China, South Korea, and Japan to shift rapidly to online learning. This study systematically reviews institutional responses via crisis and disaster management theory and the technology acceptance model. Key challenges include digital disparities, faculty preparedness, student mental health, and international student mobility restrictions. While South Korea’s robust digital infrastructure facilitated a smoother transition, China faced connectivity gaps, and Japan struggled with initial online adoption. Despite these challenges, digital learning innovations and increased student satisfaction have emerged. The findings highlight the importance of crisis preparedness, equitable technological access, and mental health support. This study provides insights for strengthening higher education resilience and informs policy recommendations for future disruptions.